2020
DOI: 10.1111/hae.13991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thromboelastometry, thrombin generation and plasma clot lysis time in patients with bleeding of unknown cause: A prospective cohort study

Abstract: Introduction: Diagnostic evaluation of patients with a bleeding tendency remains challenging, as no disorder is identified in approximately 50% of patients. An impaired interplay of several haemostatic factors might explain bleeding phenotype in these patients. Objective: To investigate whether global haemostasis assays are able to identify haemostatic abnormalities in patients with a bleeding tendency unexplained by current diagnostic laboratory tests. Materials and methods: Patients of ≥12 years with a bleed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Based on the retrospective nature of this study, this study was not subject to the Medical Research Involving Human Subjects Act and a waiver for informed consent was granted for the patient group (MEC-2020-0507). As part of the Crescendo study (Clinical Relevance and Significance of New Diagnostic Options in patients with Unexplained Bleeding) healthy individuals were recruited between July 2016 and March 2018 among employees and students of the Erasmus MC University Medical Center [9]. The Crescendo study was subject to the Medical Research Involving Human Subjects Act and approved by the Medical Ethics Committee of the Erasmus University Medical Center Rotterdam (MEC-2016-218).…”
Section: Patientsmentioning
confidence: 99%
“…Based on the retrospective nature of this study, this study was not subject to the Medical Research Involving Human Subjects Act and a waiver for informed consent was granted for the patient group (MEC-2020-0507). As part of the Crescendo study (Clinical Relevance and Significance of New Diagnostic Options in patients with Unexplained Bleeding) healthy individuals were recruited between July 2016 and March 2018 among employees and students of the Erasmus MC University Medical Center [9]. The Crescendo study was subject to the Medical Research Involving Human Subjects Act and approved by the Medical Ethics Committee of the Erasmus University Medical Center Rotterdam (MEC-2016-218).…”
Section: Patientsmentioning
confidence: 99%
“…Veen et al (2020) prospectively investigated 121 BUC/UBD patients with ROTEM (EXTEM, INTEM and FIBTEM). Thromboelastometry was within the reference range for patients with BUC 30 . Another study in 217 consecutive patients, investigated for a mild bleeding disorder, showed that ROTEM (EXTEM, INTEM and FIBTEM) was not associated with abnormal results compared to those without a mild bleeding disorder, with results mostly in the reference range, although only 4 patients had BUC/UBD in the cohort 1 …”
Section: Investigation Of Bleeding In Patients With Buc/ubd Beyond Comentioning
confidence: 84%
“…29 However, the opposite result was found in a study by Veen et al (2000), where clot lysis time was significantly longer in BUC/UBD patients compared to healthy controls. 30 shown to be a risk factor for bleeding, with a level of < 1.0 U/ml −1 found in 23% of a series of 586 consecutive patients referred for investigation of a bleeding tendency compared to 13% of controls and 10% of bloods donors (odds ratio and 95% CI, 2.04; 1.11-3.77 and 2.75; 1.39-5.42, respectively). 44 A follow-up study confirmed higher levels of plasmin-antiplasmin complexes in patients with PAI-1 < 1 U/ ml versus those with levels > 1 U/ml suggesting increased in vivo fibrinolysis in the presence of low PAI-1.…”
Section: Vwf and Blood Group Omentioning
confidence: 99%
See 2 more Smart Citations